Management of uterine cystic adenomyosis by laparoscopic surgery: case report - Cheng-Zhi Zhao; Bin Wang; Chun-yan Zhong; Shen-tao Lu; Li Lei (BMC, 2021)
Abstract Background Endometriosis of the uterine body can be manifested as diffuse solid lesions or cystic lesions. The former is common, while the latter is rare, especially for cystic adenomyosis larger than 5 cm. Case presentation A 30-year-old woman was admitted for severe and worsening dysmenorrhea. Ultrasound examination revealed a rare well-circumscribed cystic lesion about 5.5 × 4 × 5.0 cm. CA-125 level was slightly elevated. She accepted laparoscopic surgery and the adenomyotic tissues were excised. The histopathology of the specimen demonstrated the endometrial glands in the walls of cysts and an area of extensive hemorrhage can be seen in the inner wall of cyst. The patient made a good recovery after surgery and her symptoms complete resoluted. Conclusions This is a rare case of a cystic adenomyotic lesion that was treated by laparoscopic surgery.